2016
DOI: 10.1088/1361-6382/aa5203
|View full text |Cite
|
Sign up to set email alerts
|

Addendum to ‘Gravitational deflection of light and massive particle by a moving Kerr–Newman black hole’

Abstract: The gravitational deflection of test particles including light, due to a radially moving Kerr-Newman black hole with an arbitrary constant velocity being perpendicular to its angular momentum, is investigated. In harmonic coordinates, we derive the second post-Minkowskian equations of motion for test particles, and solve them by high-accuracy numerical calculations. We then concentrate on discussing the kinematical corrections caused by the motion of the gravitational source to the second-order deflection. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…For the case of no translational motion (v = 0) of the gravitational source, the four kinematical coefficients reduce to N 1 = N 2 = N 3 = N 4 = 1, and Eq. (20) becomes the second-order Kerr-Newman deflection angle of a massive particle (w < 1) [19,24] α(0, w) = 2 1 + 1…”
Section: Discussion and Summarymentioning
confidence: 99%
“…For the case of no translational motion (v = 0) of the gravitational source, the four kinematical coefficients reduce to N 1 = N 2 = N 3 = N 4 = 1, and Eq. (20) becomes the second-order Kerr-Newman deflection angle of a massive particle (w < 1) [19,24] α(0, w) = 2 1 + 1…”
Section: Discussion and Summarymentioning
confidence: 99%
“…According to GR, spacetime singularities rise various issues, both scientific and physical [46,47], by applying the nonlinear electrodynamics it is reasonable to solve these singularities by fabricating a regular BH solution [48][49][50]. He and Lin [51] have investigated the deflection of light for test particles, due to a axially moving Kerr-Newman BH with an arbitrary constant velocity that is perpendicular to its angular momentum. Additionally, it is demonstrated that here is no peculiarity of the electric field quality at the cause for the point-like particles and it has an attractive charge.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, with the first-order parameter transformation dp = dx [50] and integrating y, one can get second-order light ray as fallows…”
Section: Discussionmentioning
confidence: 99%